How to Create Value Added and Entrepreneurial Ecosystem for Sustainability of Coffee Entrepreneurs in Kerinci Regency, Indonesia: Perspective of Technology Adoption, Innovation and Capital Structure - Heppi Syofya (Mathematics Education Study Program, 2025)
Utilizing a quantitative method via structural equation modeling, this study explores the complex interrelationships between technology adoption, creativity, capital structure, value-added development, and the sustainability of coffee businesses in Kerinci. The results, based on a sample of 155 coffee entrepreneurs, show strong positive correlations between capital structure, the entrepreneurial ecosystem, and value-added development as well as their combined effects. By highlighting the interconnectedness of these elements and offering strategic insights for coffee businesses in Kerinci to improve their competitiveness and long-term sustainability, the study contributes to both theoretical understanding and practical consequences.